IT-Industry in Ukraine: Trends and Development Centers - Liudmyla NIEMETS; Kateryna SEHIDA; Kateryna KRAVCHENKO; Oleksandr NOSYRIEV; Maryna LOHVYNOVA; Olha SUPTELO (Communications of International Proceedings, 2021)
The transition from industrial to post-industrial development has intensified the development of IT technologies. Analysis of world experience shows that the economic growth of developed countries is based on the use of knowledge and high technology, and their effective combination guarantees progressive development. Aspects of IT development in Ukraine are the most relevant today, as the IT sector in recent years has dominated over other sectors of the economy in terms of development. Important questions remain: what are the regional features of the IT industry in Ukraine? What are the key poles of the IT industry in Ukraine? What are the structural and dynamic features of the development of the IT industry in the largest cities of Ukraine? What are the prerequisites and prospects for further development? This publication examines the structural and dynamic features of the IT industry in Kharkiv, Odesa, Dnipro and Lviv as the largest cities in Ukraine; With the help of SWOT-analysis the strengths and weaknesses are identified, the problems and prospects of development of the IT industry in the largest cities of Ukraine are substantiated.
Keywords: IT-industry; economy; post-industrial development; IT-service; labor market; IT- specialist; Ukraine; cities.